Text Redundancy in Academic Writing: A Systematic Scoping Review - Elena Tikhonova; Дарья Мезенцева; Petr Kasatkin (National Research University Higher School of Economics, 2024)
Background: The aim of academic writing is to effectively communicate and disseminate new knowledge and discoveries through the clear and concise expression of scientific ideas, highlighting the importance of being both brief and thorough in academic writing. The quality of this type of writing is under question. There are various sources that degrade the clarity and quality of writing. One of these aspects is redundancy, there are studies examining redundancy in written texts, however, redundancy in academic writing has received little attention. So far, there is no common  understanding of the problem in academic writing, nor a common classification, nor a clear description of the causes of this phenomenon and its effects on the quality of academic texts. Purpose: To map the existing literature on text redundancy, exploring its definitions and types, investigate the factors contributing to redundancy in academic writing, Furthermore, the article seeks to assess the impact of text redundancy on the clarity, coherence, and overall quality of academic communication. Materials and Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines and the "PCC" mnemonic (Population, Context, Concept) were applied for inclusion and exclusion criteria were utilized. A literature search was carried out in June 2024. Employing a detailed search strategy, the review engaged two electronic databases - Scopus and Google Scholar, initially identifying 252 studies. Results: 65 English-language studies addressing the text redundancy were included in the review. The synthesis of the selected research revealed that redundancy is perceived differently: as a phenomenon that reduces the quality and comprehension of the text; and a strategy that makes the text understandable and explicit. Different classification of redundancy were presented: by mode of redundancy expression and repetition, by nature, and by its role and impact.  The functions and impact on academic written communication redundancy were reviewed. Conclusion: This review explores the dual nature of text redundancy in communication, particularly within academic writing. It highlights that redundancy can enhance comprehension by reinforcing key ideas or hinder communication through excessive repetition. The study classifies redundancy into three categories: functional (beneficial), wordiness (excessive), and contextual redundancy, providing a framework for writers to manage redundancy effectively. The article emphasises the importance of balancing necessary repetition with conciseness to maintain clarity and reader engagement, as excessive redundancy may lead to reader fatigue.